Rhetoric and hermeneutics in our time : a reader - Jost, Walter, 1951-; Hyde, Michael J., 1950- (Yale studies in hermeneutics., 1997)
This book initiates a discussion among scholars in rhetoric and hermeneutics in many areas of the humanities. Twenty leading thinkers explore the ways these two powerful disciplines inform each other and influence a wide variety of intellectual fields. Walter Jost and Michael J. Hyde organize pivotal topics in rhetoric and hermeneutics with originality and coherence, dividing their book into four sections: Locating the Disciplines; Inventions and Applications; Arguments and Narratives; and Civic Discourse and Critical Theory. For readers across the humanities, the book demonstrates the usefulness of rhetorical and hermeneutic approaches in literary, philosophical, legal, religious, and political thinking.